Case of Dilated Cardiomyopathy in Combination with Left Atrial Myxoma and Left Atriomegaly (Rare Clinical Case) - Volodymyr V. Popov; Oleksandr O. Bolshak; Valery Zh. Boukarim; Olena V. Khoroshkovata; Oleksii M. Gurtovenko (Ukrainian Journal of Cardiovascular Surgery, 2022)
Case description. A 41-year-old male patient F. was admitted to the Department ofSurgical Treatment of Ac-quired Heart Diseases of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with a diagnosis: Dilated cardiomyopathy. Mitral-tricuspid insufϐiciency. Left atrial myxoma. Left atriomegaly. Pulmonary hypertension. The patient was operated with heart failure symptoms of NYHA functional class IV.After a week of medical preparation and additional examination,the patient was successfully operated on (remov-al of the left atrial myxoma, imposition of support rings on the left and right atrioventricular openings, paraanular plicacy of the left atrium). The postoperative period proceededwithout signiϐicant complications. On the 12th day after the operation, the patient was discharged in satisfactorycondition. In the remote period the patient died suddenly 3 years later.Conclusion. Taking into account the initial serious condition of a patient with advanced heart disease with a reduced left ventricular ejection fraction, left atriomegaly (7.8 cm), pulmonary hypertension (50 mm Hg) and comorbidities, complex reconstruction of the left heart in atriomegaly and ventriculomegaly leads to an improvement in the functional state of the myocardium and morphometric indicators of left atrium and left ventricular ejection fraction.